Characterization of patient’s inflammatory pulpal diseases. - Ana Gloria Vázquez de León; Clotilde de la Caridad Mora Pérez; Ana Isabel Palenque Guillemí; Nora Sexto Delgado; Mercedes Cueto Hernández (Medisur)
Background: Pulpal diseases are the most common entities in the dentist emergency consultation. For a correct indication of the treatment, it is very important to establish an accurate diagnosis. Objective: to characterize carrier patients with inflammatory pulpal disease. Methods: a descriptive, prospective cases series study which included 222 patients who came to the dentistry emergency consultation in Area I health policlinic. Age, type of disease, cause, more implicated teeth in the disease, visits, and previous treatments were the variables included. Results: there was no difference at all regarding sex. The most affected group of age was from 35 to 59 years old. The inferior molars were the most affected teeth. The main cause was dental cavities. Obturation was the previous treatment more presented. 46% of the patients attended the dentist in more than one occasion with the same process. Acute irreversible pulpitis was the most predominant pulpal disease. Conclusions: The most common pulpal diseases in our milieu was the acute irreversible pulpitis among the ages 35 and 59 years old.